DISEASES OF DENTAL HARD TISSUES AND THEIR IMPORTANCE IN THE HUMAN BODY (International journal of medical sciences, 2025)
In this article, we review common dental hard tissue diseases, such as caries, dental erosion, and endemic fluorosis, highlighting their impact on the oral cavity and the importance of early detection and intervention in maintaining dental integrity. By examining the specific characteristics and treatment options of these hard tissue diseases, we can increase knowledge and awareness of oral diseases that require attention and prompt treatment to maintain healthy teeth and gums.